0060 Investigating Latent Errors In The Operating Theatre Using High Fidelity Simulation. (1st November 2014) - Welfare, Emma; Lacasia-Purroy, Carmen; Groom, Peter; Mercer, Simon
Abstract : Background: In situ simulation based training in healthcare is becoming increasingly popular 1 . The advantages of utilising this mode of education include the opportunity to identify latent errors within the system, environment and team. This is of particular use in high risk and infrequent situations and allows improvement in patient safety and also team knowledge and skill. A previous exercise at Aintree Hospital identified particular logistical and environmental latent errors in an unexpected massive haemorrhage 2 . The National Audit Project 4 run by the Royal College of Anaesthetists highlighted the need for regular multidisciplinary drills for the unanticipated difficult airway 3 . Following this, in situ scenario based training utilising high fidelity simulation has been organised to incorporate the surgical, anaesthetic and critical care directorates at Aintree Hospital. Focus will be placed upon practising existing standard operating procedures, national guidelines and recent changes within our local practices. We would like to present the findings of this event. Methodology: Using a mix of actors and high fidelity mannequins the following scenarios will be undertaken: - Malignant hyperpyrexia. - Unanticipated difficult airway. - WHO checklist training incorporating recent local changes Each scenario will be video recorded. Feedback will focus on human factors and identifying latent errors. Results: By performing these high risk and uncommon scenarios within the clinical environment, and by utilising the required facilities and teams, we hope to identify any latent errors which may be present. Potential Impact: Detection of latent errors within healthcare is vital to improve patient safety and training for the clinical team. In situ simulation based training is well placed to support this. 4 Our aim is to highlight any latent errors within our system and environment whilst improving the knowledge of existing hospital standard operating procedures and confidence in dealing with these anaesthetic emergencies. References: Mercer SJ, Wimlett S. In-Situ Simulation. Bulletin of the Royal College of Anaesthetists 2012;76:28–30 Beament T, Mercer SJ, Lacasia C. In-situ simulation for teamwork teaching and testing of a standard operating procedure for unexpected major haemorrhage in a large University Teaching Hospital. Belfast;2014:1–50. Cook TM, Woodall N, Frerk C. Fourth National Audit Project. Major complications of airway management in the UK: results of the Fourth National Audit Project of the Royal College of Anaesthetists and the Difficult Airway Society. Part 1: Anaesthesia. British Journal of Anaesthesia . 2011;106(5):617–31 Henriksen K, et al . In SituIn Situ Simulation: Challenges and Results. Rockville (MD): Agency for Healthcare Research and Quality (US);2008